Informal Information Gathering Techniques for Active Reading - Hinckley, Ken; Bi, Xiaojun; Pahud, Michel; Buxton, Bill (CHI '12 Proceedings of the SIGCHI Conference on Human Factors in Computing Systems, 2012)
GatherReader is a prototype e-reader with both pen and multi-touch input that illustrates several interesting design trade-offs to fluidly interleave content consumption behaviors (reading and flipping through pages) with information gathering and informal organization activities geared to active reading tasks. These choices include (1) relaxed precision for casual specification of scope; (2) multiple object collection via a visual clipboard; (3) flexible workflow via deferred action; and (4) complementary use of pen+touch. Our design affords active reading by limiting the transaction costs for secondary subtasks, while keeping users in the flow of the primary task of reading itself.